Automatic Navigation for A Mobile Robot with Real Time Depth Kinect Sensor and Map Database - Uroidhi, Ali; Mardiyanto, Ronny; Purwanto, Djoko (JAVA Journal of Electrical and Electronics Engineering, 2016)
The ability view and remember the conditions surrounding is important in navigation. Ability of the kinect sensor have limitations viewing angles, and limitations reading the distance. Due to not all objects can reflect laser light very well. This research the proposed navigation system uses data of kinect depth and databases map. The experiment uses a mini computer (raspberry pi 2) to process data of kinect. Average processing each frame is 379.73 ms, the processing speed is not too fast, but navigation mobile robot can be resolved.